Immune hemolytic anemia associated with the use of immune checkpoint inhibitors: a scoping review - Hernandez-Martinez, Juan-Manuel; Rios-Garcia, Eduardo; Palomares-Palomares, Cittim B.; Arrieta, Oscar (Frontiers in Immunology, 2025)
BackgroundImmune-hemolytic anemia (IHA) is a rare immune-related adverse event (irAE) in cancer patients treated with immune-checkpoint inhibitors (ICIs). Although several cases of ICI-associated IHA have been reported, few attempts have been made to collate available information. This scoping review aims to provide a comprehensive description of the clinical features of ICI-associated IHA.MethodsPubMed and Web of Science Core Collection databases were searched for articles published in English from January 2006 to January 2025 on ICI-associated IHA. Only full-text publications reporting the clinical characteristics of patients with ICI-associated IHA were included. Two authors independently assessed the search results for eligibility and extracted the following information: author, publication year, patient characteristics, and IHA features.ResultsAmong 54 publications, published between July 2014 and March 2024, 92 cases of ICI-associated IHA were identified, revealing a high proportion of cases in patients with melanoma (45.2%) and non-small-cell lung cancer (31%). Approximately half of the cases occurred in patients receiving ICIs as first-line systemic therapy, with IHA manifesting after a median of 3 cycles. The most frequent triggering ICIs were pembrolizumab (41.3%) and nivolumab (26.1%). A high proportion of cases involved patients with a medical history of hematolymphoid tumors (34.8%), hypertension (15.2%), and anemia/AIHA (15.2%). Initial management involved ICI discontinuation (94.6%), high-dose glucocorticoids therapy (97.8%), and transfusion support (63%), with treatment responses achieved in most cases (91.3%). Only 2 cases reported fatal outcomes. IHA relapse was documented in only 7 of 23 (30.4%) patients who were rechallenged with an ICI.ConclusionsTo the best of our knowledge, this is the largest scoping review of population-based studies, case reports, and case series on ICI-associated IHA. The evidence reviewed suggests that patients with specific comorbidities may be at higher risk of developing ICI-associated IHA. In the absence of predictive tools to individually estimate the risk of this complication, a list of frequently reported co-occurring conditions in cases of ICI-associated IHA may help select patients who could benefit from closer surveillance.